1997
DOI: 10.1359/jbmr.1997.12.9.1368
|View full text |Cite
|
Sign up to set email alerts
|

Articular Chondrocytes Produce Factors That Inhibit Maturation of Sternal Chondrocytes in Serum-Free Agarose Cultures: A TGF-β Independent Process

Abstract: Under normal conditions, articular chondrocytes persist throughout postnatal life, whereas "transient" chondrocytes, which constitute the bulk of prenatal and early postnatal cartilaginous skeleton, undergo maturation, hypertrophy, and replacement by bone cells. The mechanisms regulating the markedly different behavior and fate of articular and transient chondrocytes are largely unclear. In the present study, we asked whether articular chondrocytes possess dominant antimaturation properties which may subtend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 42 publications
6
54
1
Order By: Relevance
“…Resting chondrocytes in the growth plate and articular chondrocytes maintain their nonhypertrophic phenotype by active inhibition of terminal differentiation, and soluble factors have been discussed as the main mediators of this action (17)(18)(19)30). This encouraged us to evaluate whether articular chondrocytes can teach MSCs to become stable chondrocytes, either by direct or indirect coculture, during TGF␤-driven in vitro chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resting chondrocytes in the growth plate and articular chondrocytes maintain their nonhypertrophic phenotype by active inhibition of terminal differentiation, and soluble factors have been discussed as the main mediators of this action (17)(18)(19)30). This encouraged us to evaluate whether articular chondrocytes can teach MSCs to become stable chondrocytes, either by direct or indirect coculture, during TGF␤-driven in vitro chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, coculture experiments have demonstrated that immature or articular chondrocytes produce soluble factors that are able to suppress the terminal differentiation of maturing growth plate chondrocytes in vitro (17)(18)(19). This indicates that resting chondrocytes maintain their stable phenotype by actively inhibiting terminal differentiation and could potentially teach differentiating MSCs to become stable chondrocytes in coculture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as mechanical loading, controlling cell and matrix interactions, and engineered biomaterials have been investigated toward this end, yet only modest improvements have been seen. 9 Recent studies indicate that paracrine factors released by articular chondrocytes are able to induce the chondrogenesis of MSCs [10][11][12] and inhibit the terminal differentiation of growth plate chondrocytes 13,14 as well as hypertrophy of MSCs in coculture. 11,15 However, there have been few studies examining the effects of human MSC/chondrocyte coculture on the development of the functional properties of tissue engineered cartilage as well as MSC hypertrophy using a 3D scaffold system such as these HA hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…The cephalic and Caudal (one third part of the tip region) of sterna were dissected as described by [12]. Tissues were finely diced and pre-incubated for 30 min at 37 o C with Bacterial collagenase type 1A (10mg/ml) purchased from Sigma chemical Co., Dorset U.K. and Trypsin (0.4mg/ml) GIBCO (BRL) in minimal essential medium.…”
Section: 1: Chondrocytes Culturementioning
confidence: 99%